Use of EEG Technique in a Cognitive Process Study- A Review (ELEKTRIKA- Journal of Electrical Engineering, 2022)
Cognitive processes have been widely studied using non-invasive electrical recording from the scalp called electroencephalograms (EEGs). This paper attempts to review cognitive process studies using EEG techniques according to the Layered Reference Model of the Brain (LRMB). Based on the LRMB, there are six layers of cognitive processes: Layer 1 (Sensation), Layer 2 (Memory), Layer 3 (Perception), Layer 4 (Action), Layer 5 (Meta cognitive function), and Layer 6 (Higher cognitive function). Each layer of cognitive processes will be presented with a few example research studies. Valuable information from research studies, such as the electrode of interest, task assessment used and EEG analysis applied, will be indicated and discussed to help the reader understand and select the appropriate task assessment and EEG analysis. All extracted EEG information can be extended for use in machine learning.